Study On Users' Awareness Of Facebook Privacy Policy And Settings - Obada Adnan Bayan
ABSTRACT Social networks users’ increased rapidly due to social communication services that offered by these networks. One from the most important challenges faced by the developing of social communication services is the privacy of users’ information. The social network providers offer many systematical settings to improve the information privacy based on clear and known policies; many users have not enough ICT skills and knowledge to manage their privacy settings efficiently which minimize the privacy performance of social communication services. The main aim of this research is to analyze the weakness of ICT skills of Facebook users in order to provide effective training solutions to maximize the users’ skills of using ICT settings to private their social information. The quantitative approach using questionnaire is used to analyze the main ICT skills weakness of Facebook users’ through collecting the necessary data from undergraduate students of University Sains Islamic Malaysia (USIM). The main outcome of this research is developing training module to maximize the awareness of the Facebook users’ in order to manage their privacy setting efficiently. The proposed module is evaluated through measure the users’ awareness after gathering the training data; the researcher uses post questionnaire for the purpose of module evaluating. The Pearson correlation and R square coefficients using SPSS calculated to measure the users’ behaviors differences before and after gather the proposed module. The results provide that the users’ have more positive behaviors’ of privacy activates after learn the proposed module contents. The results of this research improve that users need to learn the using of Facebook privacy settings efficiently and understand the Facebook privacy policy accurately in order to maximize the privacy awareness and enhance the privacy behaviors of Facebook users.